2014
DOI: 10.5935/0034-7167.20140037
|View full text |Cite
|
Sign up to set email alerts
|

The family in the practices of Family Health teams

Abstract: ReSUmOEstudo exploratório, qualitativo, cujo objetivo foi analisar o atributo "centralidade na família" na Estratégia Saúde da Família (ESF), buscando examinar como o contexto familiar é considerado nas práticas de saúde dos profissionais a partir da análise das práticas de saúde direcionadas às famílias na cidade de Manaus-AM. Utilizou como técnicas de levantamento de dados a entrevista, a observação participante e o grupo focal. Os informantes foram profissionais das equipes da Estratégia Saúde da Família (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
5
0
5
Order By: Relevance
“…Outro atributo derivado, a orientação familiar (PCATool-Brasil), compreendida como avaliação das necessidades considerando o contexto familiar (2) teve forte orientação da APS no geral, porém resultados diferentes foram observados em outros estudos que constataram pouca incorporação da família nas práticas assistenciais e desinteresse dos profissionais em conhecer as condições de vida do paciente e seus familiares (21)(22) .…”
Section: Resultsunclassified
“…Outro atributo derivado, a orientação familiar (PCATool-Brasil), compreendida como avaliação das necessidades considerando o contexto familiar (2) teve forte orientação da APS no geral, porém resultados diferentes foram observados em outros estudos que constataram pouca incorporação da família nas práticas assistenciais e desinteresse dos profissionais em conhecer as condições de vida do paciente e seus familiares (21)(22) .…”
Section: Resultsunclassified
“…It is highlighted that the proper start for the prenatal make it easier the access to diagnostic and therapeutic methods for many diseases that can influence directly in health of the mother and fetus (18) . However, studies point out how difficult the early approach to the pregnant, what negatively impacts the number of appointments and quality of care (19)(20) .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 34 participants in the research, 29 are women, with the majority being: mulatto (13), married (15), housewives (14), with complete secondary education (12), income of up to one minimum wage (19), does not receive social assistance (22). With mean of: 48 years of age, ranging from 20 to 82 years of age, four children, 17 years of residence in the area of the FHU and nine years of registration in the FHU.…”
Section: Resultsmentioning
confidence: 99%
“…This justifies that the difficulty of implementing a family approach in individual service stems from the need to know all members of the family, which seems to immobilize the professionals who do not incorporate the centrality in the family and prevents that it is seen as the center of attention (15) . The study also showed that in the nursing and medical appointments with persons with hypertension, for example, in which case there is family diathesis, the approach remained focused on the individual, observing that the dietary and hygienic guidelines recurrently focused on the sick individual, excluding the family from the context of prevention (15) . It is emphasized the need for a comprehensive practice of care that goes beyond the procedures and techniques, so the care is permeated by the establishment of bond and coresponsibility of the user with his or her health and by the guarantee of the right to health.…”
Section: Discussionmentioning
confidence: 99%